Double Reflexes In North-Western Bantu And Their Implications For The Proto-Bantu Consonant System - Philippson, Gerard (My University, 2022)
A number of languages in the north-westernmost area of the Bantu domain have been claimed to present two different reflexes of originally unitary Proto-Bantu (PB) phonemes. A solution to this surprising situation has been sought in the presence of some assumed phonological conditioning, whereas other authors have proposed to reconstruct new proto-phonemes. The present chapter establishes that for voiced PB phonemes, a tonal conditioning can indeed be found; but for voiceless PB phonemes, the situation is more confused, and specifically there emerges a small but consistent sub-group of reconstructed stems which escape the general “weakening” of the proto-phoneme *t, without any obvious conditioning. The hypothesis is that according to a wave model, those items were not touched by the weakening innovation at the time of its spread.
Keywords: Proto-Bantu; Reflexes; North-Western Bantu